2011
DOI: 10.1007/s00330-011-2228-x
|View full text |Cite
|
Sign up to set email alerts
|

Signal profile on Gd-EOB-DTPA-enhanced MR imaging in non-alcoholic steatohepatitis and liver cirrhosis induced in rats: correlation with transporter expression

Abstract: Our findings showed that the mrp2 expression in cirrhosis increases in comparison with NASH, and there was a paradoxical correlation between the fibrosis rate and mrp2 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 28 publications
2
28
0
Order By: Relevance
“…74,180 This is supported by reports of reduced biliary excretion of acetaminophen glucuronide and pemetrexed in rats, consistent with impaired Mrp2 function. 181,184 These findings corroborate enhanced hepatic retention and a prolonged half-life of the liver contrast agent gadolinium ethoxybenzyl diethylenetriamine pentaacetic acid (Gd-EOB-DTPA) in NASH-induced rats. 184 In contrast to Hardwick et al, who reported an increase in total MRP2 in human liver biopsies, a recent study reported decreased MRP2 protein in livers from NASH patients, which correlated inversely with progression of NAFLD.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…74,180 This is supported by reports of reduced biliary excretion of acetaminophen glucuronide and pemetrexed in rats, consistent with impaired Mrp2 function. 181,184 These findings corroborate enhanced hepatic retention and a prolonged half-life of the liver contrast agent gadolinium ethoxybenzyl diethylenetriamine pentaacetic acid (Gd-EOB-DTPA) in NASH-induced rats. 184 In contrast to Hardwick et al, who reported an increase in total MRP2 in human liver biopsies, a recent study reported decreased MRP2 protein in livers from NASH patients, which correlated inversely with progression of NAFLD.…”
Section: Introductionmentioning
confidence: 53%
“…181,184 These findings corroborate enhanced hepatic retention and a prolonged half-life of the liver contrast agent gadolinium ethoxybenzyl diethylenetriamine pentaacetic acid (Gd-EOB-DTPA) in NASH-induced rats. 184 In contrast to Hardwick et al, who reported an increase in total MRP2 in human liver biopsies, a recent study reported decreased MRP2 protein in livers from NASH patients, which correlated inversely with progression of NAFLD. 185,180 However, much of the increased MRP2 in this study was only partially glycosylated; complete glycosylation of MRP2 is required for plasma membrane trafficking.…”
Section: Introductionmentioning
confidence: 53%
“…Cirrhotic nodules that are hyperenhanced in the arterial phase have been reported, although the mechanism is unclear because cirrhotic nodules do not show histologic evidence of neo-arterialization (123). Since OATP expression is preserved, cirrhotic nodules typically have similar signal intensity to surrounding liver parenchyma in the hepatobiliary phase after hepatobiliary contrast agent administration (124) or they may appear subtly hyperintense relative to cirrhotic scars, which do not contain hepatocytes and hence do not uptake the agents. Some cirrhotic nodules may be markedly more hyperintense in the hepatobiliary phase than background nodules, presumably because they have sufficient hepatocellular function to take up the agent but not to excrete it (125).…”
Section: Cirrhotic Nodulesmentioning
confidence: 99%
“…Recently, several imaging techniques have been used to noninvasively assess NAFLD. For example, Gd‐EOB‐DTPA‐enhanced magnetic resonance imaging (MRI) has shown the liver signal profile of NASH to be different from that of cirrhosis in rats . Diffusion‐weighted (DW) MRI on the basis of the intravoxel incoherent motion (IVIM) theory in patients with type 2 diabetes has revealed that steatosis can affect diffusion parameters and perfusion fraction .…”
mentioning
confidence: 99%